Regional Election and Covid-19: Evidence in Central Kalimantan - Anyualatha Haridison; Jhon Retei Alfri Sandi; Suprayitno Suprayitno; Imanuel Jaya (Budapest International Research and Critics University, 2021)
On December 9, 2020, people in Indonesia, especially in Central Kalimantan, participated in holding regional head elections simultaneously. In the Regional Election (Pilkada) on December 9 in Kalimantan, there were 2 elections, namely the regional head election for the governor and Deputy Governor of Central Kalimantan for the period 2021-2025 and the election for the regional head of the Regent/Deputy Regent for the period 2021-2025 in East Kotawaringin Regency. The hustle and bustle of implementing the simultaneous regional elections on 9 December 2020 has differences from the previous regional head elections, this is because the implementation of the 9 December 2020 regional elections was held amid the pandemic threat of covid-19 (coronavirus disease -19). Even though it went through a long process, the pros and cons covered the election policy for the simultaneous regions, in the end, the elections were still held on December 9, 2020. Apart from Central Kalimantan, in Indonesia alone, there were around 270 regions that held simultaneous regional elections on 9 December 2020. The study in this paper wants to know how the regional head elections are held in Central Kalimantan, especially in the city of Palangka Raya. This is because Palangka Raya City has a history of the highest confirmed area of Covid-19 transmission. Besides, Palangka Raya as the capital of Central Kalimantan Province is a barometer of seeing the succession of simultaneous regional elections in Central Kalimantan. In its implementation, the Central Kalimantan Pilkada in Palangka Raya went well. The voter turnout in Palangka Raya City reached 63%. What is unique is that the regional elections in Central Kalimantan have increased participation amid a pandemic compared to the 2015 regional elections which were held in conditions without a pandemic. Even though the overall participation is below the target of the KPU RI, this increase needs to be appreciated.